Religiosity's Influence on Money Attitude, Self-Control, and Income in Shaping Consumptive Behavior: A Quantitative Analysis - Hartiningsih, Nadhita Bhela; Setiyono, Wisnu Panggah (Indonesian Journal of Islamic Studies, 2023)
This study employs a quantitative approach to investigate the impact of money attitude, self-control, and income level on consumptive behavior, with religiosity as a moderating variable. Using Likert scale data collection and Partial Least Squares (PLS) analysis, our findings reveal that money attitude and self-control positively influence consumptive behavior, while income level has a significant effect. Notably, religiosity moderates the relationship between self-control and consumptive behavior. These results shed light on the intricate interplay between individual financial attitudes, self-control, religiosity, and income level, providing valuable insights for researchers and policymakers seeking to understand and mitigate consumer behavior patterns. Highlights: Money Attitude and Self-Control Influence Consumption: Money attitude and self-control are significant factors shaping consumer behavior. Religiosity as a Moderator: Religiosity plays a moderating role in the relationship between self-control and consumptive behavior. Implications for Policy and Research: These findings offer insights for policymakers and researchers studying financial behavior and its societal implications. Keywords: Consumptive Behavior, Money Attitude, Religiosity, Self-Control, Income Level